El aprendizaje significativo en la asignatura de matemáticas en los niños de 4 a 5 años de la Unidad Educativa Miguel Ángel León Pontón de la ciudad de Riobamba. - Cali Armijo, María Esthela (2024)
The objective of this research work was to determine the significant learning in academic performance in the subject of mathematics in children aged four to five years at the Miguel Ángel León Pontón Educational Unit of Riobamba City, Chimborazo Province. Since the sample is thirty students, none of the study variables were manipulated, and the research methodology was based on the non-experimental and descriptive design since it only involves observing and describing the behavior of the phenomenon or subject without influencing it. The type of research was documentary, field, and qualitative research. As a data collection technique, observation was used as a guide to obtain qualitative data. Based on the results, it was determined that the didactic procedures used by the teacher for teaching mathematics to students are not generating significant learning in the area of study. Therefore, a significant learning brochure was prepared on mathematics; this material will help develop cognitive skills for the comprehensive development of children.